2023
DOI: 10.1099/ijsem.0.005839
|View full text |Cite
|
Sign up to set email alerts
|

Sugiyamaella bielyi f. a., sp. nov. and Sugiyamaella amazoniana f. a., sp. nov., two yeast species isolated from passalid beetles and rotting wood in Amazonia

Abstract: Sixteen yeast isolates representing two novel species of the genus Sugiyamaella were obtained from passalid beetles, their galleries and rotting wood collected in three sites of Amazonian Forest in Brazil. Sequence analyses of the ITS-5.8S region and the D1/D2 domains of the large subunit rRNA gene showed that the first species, described here as Sugiyamaella amazoniana f. a., sp. nov. (holotype CBS 18112, MycoBank 847461) is phylogenetically related to S. bonitensis with these species differing by 37 nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Other unpublished studies in the same biome showed that approximately 50% of the yeast species isolated from soil and passalid beetles represented candidates for novel species (A. R. O. Santos & C. A. Rosa, unpublished results;Souza et al, 2023).…”
Section: Amazonian Rainforestsmentioning
confidence: 93%
See 4 more Smart Citations
“…Other unpublished studies in the same biome showed that approximately 50% of the yeast species isolated from soil and passalid beetles represented candidates for novel species (A. R. O. Santos & C. A. Rosa, unpublished results;Souza et al, 2023).…”
Section: Amazonian Rainforestsmentioning
confidence: 93%
“…Several ascomycetous and basidiomycetous yeasts are frequently isolated from tropical forest biomes, notably the large-spored Metschnikowia species, Carlosrosaea, S. cerevisiae, Spathaspora, Sugiyamaella, Starmerella, and Wickerhamiella species as well as others that occur at lower frequencies (Barbosa et al, 2018;de Vega et al, 2014;Lachance et al, 2020;Santos et al, 2015Santos et al, , 2018Santos et al, , 2023Souza et al, 2023). Below we will review the most important works done with these yeasts, discussing their distribution and interactions with other organisms.…”
Section: Yeast Ecology In Tropical Forestsmentioning
confidence: 99%
See 3 more Smart Citations